Detection of Chlamydia Developmental Forms and Secreted Effectors by Expansion Microscopy - Kunz, Tobias C.; Götz, Ralph; Sauer, Markus; Rudel, Thomas (Frontiers in Cellular and Infection Microbiology, 2019)
Expansion microscopy (ExM) is a novel tool to improve the resolution of fluorescence-based microscopy that has not yet been used to visualize intracellular pathogens. Here we show the expansion of the intracellular pathogen Chlamydia trachomatis, enabling to differentiate its two distinct forms, catabolic active reticulate bodies (RB) and infectious elementary bodies (EB), on a conventional confocal microscope. We show that ExM enables the possibility to precisely locate chlamydial effector proteins, such as CPAF or Cdu1, within and outside of the chlamydial inclusion. Thus, we claim that ExM offers the possibility to address a broad range of questions and may be useful for further research on various intracellular pathogens.